2021
DOI: 10.5535/arm.21102
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Physical Activity in Patients With Type 2 Diabetes Mellitus: A Scoping Review

Abstract: To promote optimal healthcare delivery in type 2 diabetes mellitus (T2DM) following the outbreak of coronavirus disease 2019, adopting home-based physical activity (PA) is being seriously considered. Therefore, this study aims to outline the characteristics of exercise protocols for home-based PA and the challenges and limitations in implementing home-based PA in patients with T2DM. This scoping review was carried out by identifying eligible studies in six different databases (Scopus, Cochrane Library, Springe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Additionally, new practices strengthened during the COVID-19 pandemic, such as telehealth (i.e., using technology for remote monitoring of patients with T2D) [24,46], are also being adopted in the current scenario. However, the home-based exercise and T2D scenario still need greater scienti c consistency and a greater number of intervention studies [47]. Therefore, it is essential to highlight the importance of carrying out this type of intervention that will be used in the RED, involving the performance of a remotely supervised home-based exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, new practices strengthened during the COVID-19 pandemic, such as telehealth (i.e., using technology for remote monitoring of patients with T2D) [24,46], are also being adopted in the current scenario. However, the home-based exercise and T2D scenario still need greater scienti c consistency and a greater number of intervention studies [47]. Therefore, it is essential to highlight the importance of carrying out this type of intervention that will be used in the RED, involving the performance of a remotely supervised home-based exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…As the individuals included in this trial were previously sedentary, from the standpoint of patient safety, the exercises included in the home-based physical activity intervention were of low to moderate intensity, akin to activities of daily living. Therefore, taking into account the recent recommendations of Mustapa et al [ 70 ] suggesting aerobic activity with a frequency of three to five times per week at moderate intensity, along with moderate intensity free and body weight resistance training exercises, is optimal to mediate improvements in type 2 diabetic patients. It can be speculated that the prescribed exercise regimen was not sufficiently intense to mediate improvements in HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these findings oppose those of Plotnikoff et al [ 69 ], who showed significant reductions in strength and insulin control following home-based resistance training, but do concur with the observations of Krousel-Wood et al [ 68 ] using a combination of aerobic and resistance training. Once again, taking into account the recommendations of Mustapa et al [ 70 ], it can be speculated that the physical activity utilized in this trial was not of sufficient intensity to mediate improvements in hematological, blood pressure, anthropometric, or fitness indices. The current investigation nonetheless suggests that the home-based physical activity program adopted in the current investigation was ineffective in facilitating improved hematological, blood pressure, anthropometric, or fitness parameters in Saudi Arabian type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
“…On top of that, incorporating tailored physical activity (PA) in the mHealth applications is considerably pivotal for healthcare professionals (HCPs) in diabetes treatment [3]. Recent studies have also shown that the heart rate measurement while performing the PA is also an important contributor to diabetes management [4].…”
mentioning
confidence: 99%
“…Acknowledging the potential of mHealth, there is a growing interest in investigating its applications for personalised rehabilitation programmes [23,24]. Furthermore, the issues posed by the coronavirus disease of 2019 (COVID-19) pandemic, underline the critical need for remote healthcare solutions globally [4].…”
mentioning
confidence: 99%